PENGUKURAN OVERALL EQUIPMENT EFFECTIVENESS (OEE) SEBAGAI UPAYA MENINGKATKAN NILAI EFEKTIVITAS MESIN WASHER DI PT. XYZ - Mas Muhammad Rizki Aditya; Trinopi Melani; Khairul Imam A.G; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2022)
XYZ is a company engaged in the textile industry sector with its main product being gray fabric. The main part of increasing productivity is to pay attention to maintenance problems in the machine. One of the obstacles faced by companies in production is downtime which results in ineffective production levels so that production targets are not achieved and cause waste. The purpose of this study is to improve the performance of the washer machine by applying Total Productive Maintenance (TPM) and using the Overall Equipment Effectiveness (OEE) method. The research methods used are qualitative methods, case studies using design guidelines, data collection and data analysis approaches with clear evidence sources, as well as literature reviews so that a conclusion is obtained. The results showed that the availability rate of washer machines in November was more than the average for the 2020-2021 period was 86.90%. The performance rate in November had a smaller difference than the average for the 2020-2021 period of 88.59%. The rate of quality in November had a difference less than the average for the 2020-2021 period of 99.47%. The overall equipment effectiveness (OEE) in November was more than the average for the 2020-2021 period of 76.57%.